2012
DOI: 10.4103/0378-6323.93631
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema: Correlation of morphologic patterns, atopy, contact sensitization and disease severity

Abstract: Hand eczema was seen twice more commonly in men. Atopic and non-atopic patients of hand eczema had no difference in the severity of disease. Contact sensitivity to different allergens did not correlate with increased eczema severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
40
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 20 publications
14
40
4
Order By: Relevance
“…1). This finding corroborate with that of Handa et al [24] who found the most affected age group to be between 21-40 years old and that of Lysdal et al [13] between 22-32 years old. In both gender, eczema was less likely to occur in respondents who were below the age group 26-40 years and above 60 years old.…”
Section: Age and Skin Infectionsupporting
confidence: 91%
See 1 more Smart Citation
“…1). This finding corroborate with that of Handa et al [24] who found the most affected age group to be between 21-40 years old and that of Lysdal et al [13] between 22-32 years old. In both gender, eczema was less likely to occur in respondents who were below the age group 26-40 years and above 60 years old.…”
Section: Age and Skin Infectionsupporting
confidence: 91%
“…In both gender, eczema was less likely to occur in respondents who were below the age group 26-40 years and above 60 years old. Similar results were reported by Handa et al [24] and this stems from the fact that elderly have several defects in the induction and elicitation of eczema and the younger ones may only have limited exposure to irritants and allergens.…”
Section: Age and Skin Infectionsupporting
confidence: 89%
“…Similar findings were seen in number of studies. [22][23][24] Greater preponderance of hand eczema in this subset of population is possibly because of increased exposure to wet work, exposure to detergents and use of jewellery. Detergents are an important source of sensitization, proven by positive patch test results to nickel, cobalt and PPD among patients with history of exposure to detergents.…”
Section: Discussionmentioning
confidence: 99%
“…12 Handa investigated the association between sensitization and an atopic status in hand eczema patients and showed that being atopic was not a risk factor for contact allergies in patients with hand eczema. 13 Study results on the relationship between contact sensitization and a history of atopic dermatitis are also conflicting. 12,14,15 Clemmensen found similar frequencies of positive patch test reactions in patients with and without atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%